"reich an grossen, schauervollen, himmlischschönen und hinreissenden Stellen": Florian Dellers Orphée et Euridice am württembergischen Hof - Fabian, Sarah-Denise (Die Musikforschung, 2020)
Eigtheenth-century Ballet at the Württemberg court under Duke Carl Eugen primarily associated with one name: the choreographer Jean Georges Noverre - and his concept of a new dramatic action ballet, in which music plays a central role. Today, however, the composers of this music are largely forgotten and their contribution to Noverre's revolutionary ballets is underrated. One of them, the Württemberg court musician Florian Deller (1729-1773), composed the music for many of Noverre's reform ballets, including Orphée et Euridice (1763). A detailed analysis of the score maps the musical movements onto the dramatic scenes and reveals how the music is tailored to the plot and Noverre's dramaturgical concept.